2015
DOI: 10.1089/chi.2014.0143
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Compliance with a New Physical Activity Guideline for Preschool-Age Children

Abstract: Approximately one half of children in two independent samples met the guideline for PA in young children. Policies and practices designed to increase PA among preschool children are needed, given that most children are not meeting this PA guideline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
117
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(124 citation statements)
references
References 31 publications
4
117
2
1
Order By: Relevance
“…In fact, both boys and girls achieved a mean of greater than 90 minutes of MVPA/day; however, boys had a mean average of 13 minutes more in MVPA/day than girls ( p <0.001). Cross-sectional studies using older samples of children 12,43-45 found that boys engaged in significantly greater amounts of accelerometry-assessed PA than girls. The present study's finding highlights the opportunity at this developmental period to enhance PA and reduce sedentary behaviors among all children before PA levels begin to decline as they reach adolescence, particularly among girls given this decline begins in early adolescence.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In fact, both boys and girls achieved a mean of greater than 90 minutes of MVPA/day; however, boys had a mean average of 13 minutes more in MVPA/day than girls ( p <0.001). Cross-sectional studies using older samples of children 12,43-45 found that boys engaged in significantly greater amounts of accelerometry-assessed PA than girls. The present study's finding highlights the opportunity at this developmental period to enhance PA and reduce sedentary behaviors among all children before PA levels begin to decline as they reach adolescence, particularly among girls given this decline begins in early adolescence.…”
Section: Discussionmentioning
confidence: 97%
“…9-11 A recent report shows that less than half of preschoolers obtain the recommended ≥3 hours/day of total PA (light, moderate, and vigorous), with at least 1 of these hours in MVPA, recommended by leading international organizations. 12,13 Some studies indicate that Latino and African American youth are at lower odds of meeting daily PA recommendations 14,15 and higher odds of being overweight/obese. 16 For example, nationally representative U.S. data of children aged 6–11 years show that Mexican Americans engage in less MVPA.…”
Section: Introductionmentioning
confidence: 99%
“…2 Authorities in several countries, including the U.S., 3–7 have developed physical activity guidelines for young children, and studies have shown that many children aged 3–5 years in the U.S. and elsewhere fail to meet those guidelines. 811 …”
Section: Introductionmentioning
confidence: 99%
“…The National Academy of Medicine in the United States has recommended that preschool-aged children should accumulate 15 min of physical activity every hour they are in care [21]. Evidence evaluating compliance with this recommendation during care hours is lacking [22]. …”
Section: Introductionmentioning
confidence: 99%